Accuracy Constraints Improve Symmetric Bimanual Coordination for Children with and without Unilateral Cerebral Palsy. - Hung, Ya-Ching; Zeng, Wenhui (Developmental Neurorehabilitation, 2020)
Purpose: To evaluate the influence of accuracy constraints on functional symmetric bimanual coordination for children with Unilateral Spastic Cerebral Palsy (USCP). Methods: Ten children with USCP (average age: 9.6; MACS levels: I–II), ten typically developing children, and ten adults lifted a tray with a water bottle on top. Two accuracy constraints of handle size and cap condition were manipulated. Results: Children with USCP exhibited greater bilateral asymmetry in hand vertical position, timing, upper arm, and elbow control than other groups. Smaller handle decreased bilateral timing differences at lift onset and offset, and decreased bilateral elbow asymmetry at reach and lift offset. Without a cap (accuracy constraint), they showed greater trunk involvement, and less bilateral vertical position and lift offset timing differences (all p <.05). Conclusions: Children with USCP showed impaired symmetric bimanual coordination. Higher accuracy constraints improved some bimanual spatial and temporal control. Therefore, task accuracy constraints should be manipulated carefully for training.